A importância do autoconsumo na renda das famílias assentadas no Rio Grande do Sul - Jaehn, Eduardo (2019)
This paper aims to analyze the importance of self-consumption in agrarian reform settlements in Rio Grande do Sul. The characterization of self-consumption in the settlements is based on the information of the settled families present in the ATES Integrated Rural Management System, which were tabulated with the aid of Microsoft Excel software, and are composed of 9.719 records updated in 2015. This information was compared from the tabulation in seven regions of the state of Rio Grande do Sul, namely: Campaign, Central, West Frontier, Metropolitan, Missions, North and South. The analysis of the contribution of selfconsumption to household income was based on information from 62 worksheets of the Pedagogical Observation Units Network, which are classified into 5 production systems, namely: Rice, Vegetable Garden, Milk, Milk and Grains and Livestock. The economic analysis was performed by the value added method and were calculated the gross product, the intermediate cost, the depreciation, the value added distribution and the self-consumption income. The hypotheses that guide the research consider that: there are regional differences in production for self-consumption; there are differences in production for self-consumption in the different production systems practiced and; self-consumption contributes significantly to the income of settled families. The results indicate that self-consumption production is a very common practice among settled families, as over 85% record self-consumption of at least one item of animal production and almost 90% record self-consumption of at least one agricultural crop. The characterization of self-consumption also points out that there are regional differences in production for self-consumption that can be explained by the different agroecological and socioeconomic conditions of each region. The economic analysis of selfconsumption indicates that it is important in the composition of the total gross product of the production units and that there are significant differences in the production systems, in rice its contribution to the total gross product is less than 1% on average, while in the livestock system it reaches 16% on average. In the composition of the gross product of selfconsumption it is noticed the greater importance of products of animal origin, which account for more than 50% of this. The analysis also indicates that the specific dynamics of production systems impact self-consumption production, since systems with higher level of input externalization are also those with greater externalization in self-consumption production, although it is evident that in general, the production for self-consumption has a higher level of internalization compared to the production system as a whole. Conclusions indicate that self-consumption is important for settled families, it contributes to the composition of household income and that there are differences in relation to regions and production systems. There is still a need for further studies that indicate the factors that determine the particularities of production for self-consumption in rural settlements.